The effect of the ambient temperature profile in the determination of power cable ratings - Wan Mohd Zain, Wan Azimin; Nik Ali, N. H.; Hamdan, M. A.; Azis, N.; Johari, D.; Rameli, Norhidayu (IEEE, 2022)
Power cables are primarily utilized for power distribution and transmission. It is a combination of one or more individually insulated electrical conductors that are generally kept together by a sheath. The arrangement is utilized for electrical power transmission and distribution. The limitations within which a cable can be used safely are determined by cable ratings. Temperature, voltage, and current are the most common factors to determine the cable ratings. When the cables are equipped in the condition of the surrounding, the cables are likely to experience a change in their ratings as they were installed in various environmental conditions and geographical locations. The IEC Standard as the main reference is used to stimulate the current ratings when the cables are in the surrounding conditions and the effect of environmental factors such as global warming. However, as the ambient temperature has been increasing dramatically over the past years, only the ambient temperature profile which is based on a few of the world continents' profiles and also specifically the ambient temperature profile in Malaysia is studied and presented by varying ambient temperatures in the IEC Standard mathematical algorithm. The result shows that the cable capabilities to carry the current will be affected by the various ambient temperatures in different locations.